FAO/IPGRI Multi-Crop Passport Descriptors [MCPD] - Alercia, A.; Diulgheroff, S.; Metz, T.; Food and Agriculture Organization of the United Nations; International Plant Genetic Resources Institute (2001)
The List of Multi-Crop Passport Descriptors (MCPD) is a reference tool developed jointly by IPGRI and FAO to provide international standards to facilitate germplasm passport information exchange across crops. These descriptors aim to be compatible with IPGRI crop descriptor lists and with the descriptors used for the FAO World Information and Early Warning System (WIEWS) on plant genetic resources (PGR). This revised version (December 2001) of the 1997 MCPD List, provides a brief explanation of content, coding scheme and suggested fieldnames for each descriptor to assist in the computerized exchange of this type of data.